LANGUAGE ANXIETY IN CHINESE UNIVERSITY EFL LEARNERS IN VARYING LEARNING CONTEXTS - Meihua Liu (Indonesian JELT, 2012)
The present study examined Chinese university EFL learners’ anxiety in English classrooms in varying learning contexts, and causes for and impact of anxiety on their performance in English. Analyses of 215 journals and 1203 questionnaires revealed the following conclusions: (1) around a third of the whole participant sample and each university sample experienced anxiety in English class, (2) various reasons such as low proficiency in the target language, lack of vocabulary, lack of practice, lack of preparation, and poor pronunciation were responsible for anxiety in the participants, and (3) anxiety mainly debilitated the students’ performance in English and the majority of the participants felt helpless about feeling anxious when using the language in English class.